Wife’s right to her husband’s property that is disputed by them both: A juristic study - Salem, Khobaib Ali Saeed; Elbahrawi, Salah Mohamed Moustafa Moustafa; Soliman, Ragab Abou Melih Mohamed; Abdelgayed, Ahmed Fathi Ramdan (Linguistics and Culture Review, 2021)
This research study addresses the perspective of Islamic jurisprudence on the right established for a wife in her husband’s property that is disputed by them both, especially after termination of their marital relationship. The research problem lies in that many women, upon their separation from their husbands, believe that their husbands’ financial welfare was only a result of their own assistance in undertaking marital responsibilities. This research study attempts to answer the question raised in such cases: What are the rights established for women against their husband in case they claim so?. The study seeks to highlight the objectives of the Shar?‘?h behind marriage and legalization of divorce, and to illustrate the established as a woman’s right in her husband’s property which she should have shared with him or substituted him in managing, through different considerations. The significance of the study lies in the emergent need for investigating it due to contemporary occurrences. This study builds on a descriptive and deductive comparative approach, along with a referential and applied method based on the juristic maxims and Shar?‘?h objectives, drawing only on preponderant legal opinions; outweighed views and their proofs are not mentioned in this study.